Efficient trinuclear Ru(ii)–Re(i) supramolecular photocatalysts for CO2 reduction based on a new tris-chelating bridging ligand built around a central aromatic ring. Issue 6 (6th January 2020) - Cancelliere, Ambra M.; Puntoriero, Fausto; Serroni, Scolastica; Campagna, Sebastiano; Tamaki, Yusuke; Saito, Daiki; Ishitani, Osamu
Abstract : We have designed and synthesized a new tris-chelating polypyridine ligand (bpy3 Ph ) suitable to be used as a bridging ligand (BL) for constructing various supramolecular photocatalysts. Abstract : We have designed and synthesized a new tris-chelating polypyridine ligand (bpy3 Ph ) suitable to be used as a bridging ligand (BL) for constructing various supramolecular photocatalysts. This BL is a phenylene ring with three ethylene chains at 1, 3, and 5 positions, of which the other terminals are connected to 2, 2′-bipyridine moieties. The ligand bpy3 Ph has been used to prepare, according to a multi-step synthetic protocol, trinuclear supramolecular photocatalysts containing different metal subunits. In particular, the compounds Ru2Re and RuRe2 have been prepared, containing different ratios of components based on Ru(dmb)3 2+ -type and Re(dmb)(CO)3 Cl-type units (dmb = 4, 4′-dimethyl-2, 2′-bipyridine), which can play the roles of photosensitizers and catalyst units for photocatalytic CO2 reduction, respectively. The trinuclear model Ru3 and mononuclear and dinuclear Ru and Ru2 precursor metal complexes, containing free chelating sites, have also been synthesized using the same bridging ligand. The absorption spectra, redox behaviour and photophysical properties of the new species indicate that there is no strong electronic interaction among the Ru and Re units. The trinuclear complexes Ru2Re and RuRe2 could photocatalyze CO2 reduction to CO with high selectivity (up to 97%), high efficiency ( Φ CO s of 28% and 25%, respectively: BIH as a reductant), and high durability (TONCO s of 5232 and 6038, respectively: BIH as a reductant) which are the largest TONs for CO2 reduction using supramolecular photocatalysts in homogeneous solutions. The absence of negligible accumulation of the mono-reduced form of the photosensitizer indicates fast electron transfer to the catalyst unit(s) through the relatively large bridging ligand and is proposed to contribute to the outstanding photocatalytic properties of the new species, including their durability. The relevant photocatalytic behaviour of the new systems indicates new avenues for the design of extended bridging ligands capable of efficiently and functionally integrating photosensitizers and catalysts towards the preparation of new, larger supramolecular photocatalysts for selective CO2 reduction.